Effects of the culturally sensitive DEmentia Competence Education for Nursing home Taskforce (DECENT) programme in mainland China: A quasi‐experimental study. (December 2021) - Zhao, Yayi; DING, Yaping; Liu, Li; Chan, Helen YL
Abstract: Background: A number of dementia care educational programmes are developed to build nursing‐home staff's care competence in the Western culture. However, their applicability and cultural relevancy to Chinese population are questionable. This study aimed to develop and evaluate a Culturally Specific DEmentia Competence Education for Nursing home Taskforce (DECENT) programme in mainland China. Method: A multi‐centre two‐arm repeated‐measures quasi‐experimental study was conducted with 217 care staff from 10 nursing homes. Nursing homes were pair‐matched and allocated into intervention (n = 5) and control group (n = 5). Participants were allocated into intervention group (n=101) who received the DECENT programme or control group (n = 116) who received the printed educational materials according to the settings they worked. The DECENT programme comprised eight topics and was delivered through multiple pedagogical strategies by a qualified educator once per week for 60‐90 minutes over eight weeks. The study outcomes were the sense of competence in dementia care, dementia knowledge, attitudes towards people with dementia, person‐centred care in nursing homes and the severity of behavioural and psychological symptoms of dementia (BPSD) of residents with dementia and staff‐perceived disturbance. They were measured at baseline (T0 ), immediately post‐intervention (T1 ) and 3‐month after intervention (T2 ). Generalised estimating equation models were performed to analyse the effect. Result: The intervention group improved more significantly than the control group in sense of competence in dementia care both at T1 (B = 5.24, p < .001) and T2 (B = 4.43, p = .013). In terms of dementia knowledge and person‐centred care in nursing homes, the intervention group only showed significant improvement at T1 (B = 3.18, p = .001; B = 5.75, p = .018, respectively), but not at T2 ( p = .089 and .104, respectively), when compared to control group. Attitudes towards people with dementia and severity of BPSD and staff‐perceived disturbance were not significant both at T1 and T2 relative to control group. Conclusion: The DECENT programme is effective in improving nursing‐home staff's perceived dementia‐care competence. Nevertheless, continual learning and support at organisational level is needed for cultivating changes in practice and residents' outcomes.